Kitchen science lab for kids : 52 family- friendly experiments from around the house - Heinecke, Liz Lee (2014)
At-home science provides an environment for freedom, creativity and invention. In your own kitchen, it's simple, inexpensive, and fun to whip up a number of amazing science experiments using everyday ingredients. Science can be as easy as baking. Hands-On Family: Kitchen Science Lab for Kids offers 52 fun science activities for families to do together. The experiments can be used as individual projects, for parties, or as educational activities groups. Kitchen Science Lab for Kids will tempt families to cook up some physics, chemistry and biology in their own kitchens and back yards. It's the perfect resource for Girl Scout Brownies looking to earn their Home Scientist badges! Many of the experiments are safe enough for toddlers and exciting enough for older kids, so families can discover the joy of science together.